EFFECTS OF SLAB ROLLBACK ACCELERATION ON AEGEAN EXTENSION - Brun, J.-P.; Faccenna, C.; Gueydan, F.; Sokoutis, D.; Philippon, M.; Kydonakis, K.; Gorini, C. (Bulletin of the Geological Society of Greece, 2016)
Aegean extension is a process driven by slab rollback that, since 45 Ma, shows a twostage evolution. From Middle Eocene to Middle Miocene it is accommodated by localized deformation leading to i) the exhumation of high-pressure metamorphic rocks from mantle to crustal depths, ii) the exhumation of high-temperature rocks in core complexes and iii) the deposition of Paleogene sedimentary basins. Since Middle Miocene, extension is distributed over the whole Aegean domain giving a widespread development of onshore and offshore Neogene sedimentary basins. We reconstructed this two-stage evolution in 3D at Aegean scale by using available ages of metamorphic and sedimentary processes, geometry and kinematics of ductile deformation, paleomagnetic data and available tomographic models. The restoration model shows that the rate of trench retreat was around 0.6 cm/y during the first 30 My and then accelerated up to 3.2 cm/y during the last 15 My. The sharp transition observed in the mode of extension, localized versus distributed, which occurred in Middle Miocene correlates with the acceleration of trench retreat and is more likely a consequence of the Hellenic slab tearing documented by mantle tomography. The development of large dextral NE-SW strike-slip faults during the second stage of Aegean extension, since Middle Miocene, is illustrated by the 450 Km-long fault, recently put in evidence, offshore from Myrthes to Ikaria and onshore from Izmir to Balikeshir, in western Anatolia. Therefore, the interaction between the Hellenic trench retreat and the westward displacement of Anatolia started in Middle Miocene, almost 10 Ma before the propagation of the North Anatolian Fault in the North Aegean. This raises a fundamental issue concerning the dynamic relationship between slab tearing and Anatolia displacement.